1976
DOI: 10.1113/jphysiol.1976.sp011304
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypercapnia on a blood‐brain barrier mechanism in foetal and new‐born sheep.

Abstract: SUMMARY1. The effect of marked hypercapnia (arterial PCO, 100 mmHg), nonrespiratory acidosis (pH 6.95-7-15) or hypoxia (arterial PO,[10][11][12][13][14][15] upon penetration of labelled sucrose from blood into brain and c.s.f. has been investigated in exteriorized foetal sheep and new-born lambs.2. In hypercapnia there was a consistent increase in c.s.f./plasma sucrose ratio after 90 min i.v. sucrose to four to five times control. Brain/ plasma sucrose ratios were more variable. Usually there was an increase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
3

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
15
3
Order By: Relevance
“…Likewise, the increases in arterial carbon dioxide tensions in the fetuses at 60% of gestation and in the newborn lambs during the glucose infusions were similar to those during the mannitol infusions (Stonestreet et al, 2006). Although hypercapnia results in increased penetration of sucrose into the brains of fetal and newborn sheep and adult rabbits, the carbon dioxide levels in the previous reports were much higher than during glucose (Table 1) and mannitol hyperosmolality in our studies (Cameron et al, 1969;Evans et al, 1976;Stonestreet et al, 2006). The increases in the arterial carbon dioxide tensions in the fetuses at 60% of gestation and in the newborn lambs were similar and analogous to those we reported during the mannitol infusions (Stonestreet et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, the increases in arterial carbon dioxide tensions in the fetuses at 60% of gestation and in the newborn lambs during the glucose infusions were similar to those during the mannitol infusions (Stonestreet et al, 2006). Although hypercapnia results in increased penetration of sucrose into the brains of fetal and newborn sheep and adult rabbits, the carbon dioxide levels in the previous reports were much higher than during glucose (Table 1) and mannitol hyperosmolality in our studies (Cameron et al, 1969;Evans et al, 1976;Stonestreet et al, 2006). The increases in the arterial carbon dioxide tensions in the fetuses at 60% of gestation and in the newborn lambs were similar and analogous to those we reported during the mannitol infusions (Stonestreet et al, 2006).…”
Section: Discussionsupporting
confidence: 80%
“…The entry of sucrose into the c.s.f. was also increased by hypercapnia (Evans et al 1976). Hochwald et al (1973) found that c.s.f.…”
Section: Discussionmentioning
confidence: 99%
“…production. In previous studies hypercapnia has been found to increase (Ames, Higashi & Nesbett, 1965), decrease (Evans, Reynolds, Reynolds & Saunders, 1976) or have no effect (Hochwald, Malhan & Brown, 1973) on c.s.f. formation.…”
Section: Discussionmentioning
confidence: 99%
“…Dziegielewska, Evans, Malinowska, M0llgard, . This permeability is increased under hypercapnic conditions (Evans, Reynolds, Reynolds, & Saunders, 1976;Habgood, 1990 (Sakurada, Kennedy, Jehle, Brown, Carbin & Sokoloff, 1978). These measurements were based on the Fick principle as described by Kety & Schmidt (1945), and the autoradiography techniques were similar to those first described by Reivich, Jehle, Sokoloff & Kety (1969).…”
Section: Introductionmentioning
confidence: 99%